Methods of RNA purification. All ways (should) lead to Rome - Matrasová, Ivana; Vaníčková, Zdislava; Šedo, Aleksi (Folia biologica (Praha), 2009)
Ribonucleic acid (RNA) represents an important target of a wide array of laboratory anal yses. Thus, RNA purification is a critical first preceding step of a number of preparative and analytical methods, important particularly in diagnostics of dozens of viral, bacterial, and parasitic diseases, dia gnosis of inherited disorders, and tumours, as well as in basic research. To provide relevant and reliable results, techniques of molecular biology used for such purposes require pure and intact molecules of purified RNA. Moreover, RNA has to be purified effectively and reproducibly from various heterogeneous materials such as fresh or frozen tissues, cell lines, PCR products or long-term chemically preserved samples. Principally, methods of RNA purification can be divided into three groups. The first group of methods is based on organic phenol:chloroform extraction. The second group encompasses methods of RNA purification by means of its ability to bind specific surfaces in the presence of chaotropic salt, and the third group includes methods exploiting RNA isolation on isopycnic gradients. Although RNA can be isolated from either prokaryotic or eukaryotic organisms, this review is to give out a basic outline of methods available for eukaryotic, with emphasis on mammalian, tissues.
Keywords: lidé; adsorpce; Animals; Solvents; RNA; zvířata; Adsorption; Humans; rozpouštědla